2019
DOI: 10.1002/cam4.2530
|View full text |Cite
|
Sign up to set email alerts
|

Identification and external validation of a novel miRNA signature for lymph node metastasis prediction in submucosal‐invasive gastric cancer patients

Abstract: Endoscopic resection (ER) has been increasingly performed in the treatment of early gastric cancer (GC). However, lymph node metastasis (LNM) can cause treatment failure with ER, especially in T1b patients. Here, we attempted to develop a miRNA‐based classifier to detect LNM in T1b patients. Based on high‐throughput data from The Cancer Genome Atlas, we identified 20 miRNAs whose expression significantly changed in T1‐2 GC with LNM vs T1‐2 GC without LNM. We then developed a miRNA signature to predict LNM of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies have shown that miR-940 has high sensitivity and specificity in the diagnosis of diseases such as GC 4 and breast cancer. 33 In addition, miR-940 can also be used as a signature model with other miRNAs for the diagnosis of submucosal invasive GC, 48 PAAD, 20 NPC, 7 UCB, 28 Wilms tumor (WT), 49 and other diseases ( Table 3 ).…”
Section: Mir-940 As a Potential Marker And Therapeutic Targetmentioning
confidence: 99%
“…Studies have shown that miR-940 has high sensitivity and specificity in the diagnosis of diseases such as GC 4 and breast cancer. 33 In addition, miR-940 can also be used as a signature model with other miRNAs for the diagnosis of submucosal invasive GC, 48 PAAD, 20 NPC, 7 UCB, 28 Wilms tumor (WT), 49 and other diseases ( Table 3 ).…”
Section: Mir-940 As a Potential Marker And Therapeutic Targetmentioning
confidence: 99%
“…Some studies used biomarkers to predict the risk of lymph node metastasis in early gastric cancer. Ma et al (16) constructed a risk stratification model composed of four mi-RNAs (miR153-3p, miR-708, miR-940 and miR-375). Chen et al (17) predicted lymph node metastasis based on collagen signaling in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%